CONCEPT OF MATHEMATICAL LOGIC REASONING IN QURAN - Hamidah binti Maidinsah; Noor Ezzah binti Ishak; Nur Laila binti Mohamad Noorisham (Journal of Islamic, Social, Economics and Development, 2022)
Muslims are considered a cultural group that holds the Quran as their guidance and practice regulations accordingly as a way of life. They apply mathematical knowledge to solve problems as they embrace and practice Quranâ€™s teaching. One of the mathematical cognitive domains that occurs in Quran is logical reasoning. The objective of the research is to discuss several verses in the Quran related to mathematical logic. This study uses an exploratory design on several selected verses. The results revealed that verses such as Al-Fatihah (1: 6-7), Al-Anfal (8: 29), Thaha (20:124), Az-Zukhruf (43:36), and Al-Jin (72:17) can be applied to logic reasoning using logic operation such as â€œnotâ€, â€œandâ€, â€œorâ€ as well as â€œimplicationâ€. A statement has a True or False value but not both. An equivalent statement is proved using a truth table. By using rules of logic, the statements of the verses can be written in simple mathematical symbols besides giving precise meaning. The results of this study will allow diversification in developing high school and higher learning institution learning material related to mathematical logic reasoning and Quran.